A ferritin-like diiron oxygenase BioE initiates bacterial biotin synthesis, a promising antivirulence target - Yongchang Xu; Meng Zhang; Yingying Fu; Xiaoqiang Yang; Man Huang; Qiuying Qin; Yanhua Kang; Xinyu Su; Jiaming Fang; J. Martin Bollinger; Zhi Ruan; Youjun Feng (Proceedings of the National Academy of Sciences, 2025)
Biotin is an essential enzyme cofactor for intermediary metabolism, and its importance is reflected by the multiplicity of bacterial pathways to its universal precursor, pimelic acid. Here, we report identification of a fourth pimeloyl pathway in the rare but clinically important pathogens Elizabethkingia and Chryseobacterium . This pathway is encoded by two associated structural genes, bioE and bioL . BioE is a ferritin-like nonheme diiron oxygenase that oxidatively cleaves saturated C n (n = 14, 16, 18) fatty acyl coenzyme A (CoA) or acyl carrier protein (ACP) substrates to pimeloyl-CoA/ACP and the free C n-7 acid. The catalytic activity was demonstrated by both in vitro enzymatic assays and the capacity of the bioE gene to complement the genetic defect of an Escherichia coli biotin indicator strain that cannot produce the pimeloyl precursor. BioL, an unusual MocR-type bifunctional transcription factor, negatively regulates bioE expression in response to binding of the downstream intermediate 7-keto-8-aminopelargonic acid. Disruption of bioE in Elizabethkingia meningoseptica and Chryseobacterium indologenes makes them auxotrophic for biotin, impairs biofilm formation, and attenuates bacterial infectivity. Taken together, our findings expand enzymatic diversity of biotin biosynthesis and suggest that selective inhibition of this BioE pathway could provide a therapeutic strategy against recalcitrant nosocomial infections caused by these multidrug-resistant pathogens.